2023
DOI: 10.1038/s41598-023-28392-8
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength is inversely associated with augmentation index in patients with type 2 diabetes

Abstract: Handgrip strength (HGS) is a measure of overall skeletal muscle strength and is used to identify risks for cardiovascular disease and mortality. Furthermore, HGS is an indicator of arterial stiffness that leads to atherosclerotic cardiovascular disease. This study aimed to examine the relationship between HGS and augmentation index (AIx) in patients with type 2 diabetes. A cross-sectional study was conducted to examine patients with type 2 diabetes whose HGS and AIx were measured in our hospital. AIx was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Age-related decreases in muscle strength, mass, and function are referred to as sarcopenia, which can result in reduced physical performance and an increased risk of adverse health outcomes. Among these, HGS, which indicates skeletal muscle strength [ 2 ], is a key factor of sarcopenia and is used as a biomarker, which is consistent in explaining bone mineral density, fractures, quality of life, diabetes, arterial stiffness, cardiovascular disease, and all-cause mortality [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Dixon et al showed that weak grip strength is associated with an increased risk of vertebral fracture and poor bone mineral density in the hips and spine in women [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related decreases in muscle strength, mass, and function are referred to as sarcopenia, which can result in reduced physical performance and an increased risk of adverse health outcomes. Among these, HGS, which indicates skeletal muscle strength [ 2 ], is a key factor of sarcopenia and is used as a biomarker, which is consistent in explaining bone mineral density, fractures, quality of life, diabetes, arterial stiffness, cardiovascular disease, and all-cause mortality [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Dixon et al showed that weak grip strength is associated with an increased risk of vertebral fracture and poor bone mineral density in the hips and spine in women [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that grip strength was lower in adults (aged ≥ 20 years) with diabetes with no history of cardiovascular disease [ 30 ]. Several studies have shown that HGS is negatively associated with arterial stiffness in non-hypertensive participants, patients with diabetes, and patients with chronic coronary syndrome [ 31 , 32 , 33 ]. Moreover, weak grip strength was associated with a higher risk of mortality from cardiovascular disease, respiratory disease, and cancer in a prospective cohort study of half a million UK Biobank participants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed both lower values of grip strength and higher values of AIx@75% than those obtained in the present study, consistent with their older age and their a diagnosis with two of the chronic pathologies that are commonly associated with an increased arterial stiffness. They observed a negative correlation between HGS/Kg and AIx@75% [ 20 , 33 ]. Another study found a negative correlation between maximum dynamic strength and AIx@75% in individuals with mobility limitations and a mean age of 68 years [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methodology and results of the present study do not permit us to determine the physiological and/or molecular mechanisms that describe the influence of HGS on arterial stiffness. However, there are common factors that may contribute to low muscle strength, as well as an increased arterial stiffness, including oxidative stress, insulin resistance, increased body fat percentage, endothelial dysfunction and the presence of higher levels of circulating inflammatory markers (elevated levels of C-reactive protein, interleukin-6, D-dimer, factor VIII) [ 33 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation